Recovery of palm carotene from palm oil and hydrolyzed palm oil by adsorption column chromatography - You, L.L.; Baharin, B.S.; Quek, S.Y.; Abdullah, M.A.; Takagi, S. (Blackwell Publishing Inc.subscrip@blackwellpub.com, 2002)
Crude palm oil and crude palm olein were hydrolyzed with lipase from Candida rugosa to produce a free fatty acid (FFA) rich oil. The percentages of FFA produced and carotene degradation after the hydrolysis process were determined. The palm oil and hydrolyzed palm oil were subsequently subjected to column chromatography. Diaion HP-20 adsorbent was used for reverse phase column chromatography at 50C. Isopropanol or ethanol, and n-hexane were used as the first and second eluting solvents, respectively. The objective of hydrolyzing the palm oil was to produce more polar FFA-rich oil in order to enhance the nonpolar carotene bind to the nonpolar HP-20 adsorbent in the column chromatography process. Hydrolyzing palm oil with lipase from Candida rugosa gave 30- and 60- fold, respectively, of FFA in the crude palm oil and crude palm olein in 24 h at 50C. Approximately, 15.56 and 17.48% of carotene degraded in crude palm oil and crude palm olein, respectively. For column chromatography, using isopropanol or ethanol as the first eluting solvent, unhydrolyzed oil and hydrolyzed oil showed the carotene recovery in fraction two (carotene-rich fraction) of about 36-37 and 90-96%, repectively. Over 90% of carotene recovery was obtained from hydrolyzed palm oil reflecting an increase of about 55% over unhydrolyzed crude palm oil.